Dual-Band Performance Evaluation of Time-Modulated Circular Geometry Array With Microstrip-Fed Slot Antennas - Zenon Medina; Alberto Reyna; Marco A. Panduro; Omar Elizarraras (IEEE Access, 2019)
This paper applies time modulation to deal with the design of dual-band antenna arrays in a circular geometry using a micro-strip-fed slot antenna as an element in the frequencies of 2.4 and 5.5 GHz. The motivation for this paper is to exploit the properties and advantages of time-modulated arrays in a dual-band scenario considering a circular geometry. This design considers the optimization of the time switched sequences of the antenna elements in the circular geometry for both operation frequencies. The design process to find the optimal switch- ON intervals of the circular array is carried out by means of the method of differential evolution and particle swarm optimization. The main contribution to the field of this paper is the dual-band performance evaluation of circular antenna arrays considering time modulation and measurements of the antenna element pattern. The performance evaluation and the results and discussion are achieved in terms of the radiation pattern with the measured antenna element, sidelobe level, sideband levels, switching times and efficiency.